Application of dynamic hysteresis band height control to improve output voltage transient in boost and Positive Buck-Boost converters - Boora, A.; zare, F.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
This paper presents dynamic hysteresis band height control to reduce the overshoot and undershoot issue on output voltage caused by load change. The converters in this study are Boost and Positive Buck-Boost (PBB) converters. PBB has been controlled to work in a step up conversion and avoid overshoot when load is changed. Simulation and experimental results have been presented to verify the proposed method.